Small-Scale Fish Farming and Poverty Reduction in Some Selected States in Southeast, Nigeria - OKOYE, Lucky I.; KALU, Chris U.; UZONWANNE, Maria C.; EZENEKWE, R. Uju (Socialscientia: Journal of Social Sciences and Humanities, 2023)
Despite the implementation of numerous poverty reduction programmes by successive governments, poverty remains endemic and pervades every geo-political zone in Nigeria. The poverty situation, coupled with the low uptake of fish farming technology in the south-east zone necessitated the need to examine the impact of small-scale fish farming on poverty reduction in selected states of the south-east geo-political zone of Nigeria. The dependent variable of the study is poverty reduction, proxy by household expenditure, while the independent variable is the small-scale fish farming, proxy by income, employment, food security, and consumption multiplier. The mixed-method research design comprising of quantitative (questionnaire) and qualitative (focus group discussion and in-depth interview) were used for data collection, while descriptive and inferential statistics were used in data analysis. A total of two hundred and seventy (270) small-scale fish farming households were selected from Anambra, Ebonyi, and Imo State as the population sample, using the multi-stage cluster sampling technique. Four hypotheses were tested using the Kolmogorov-Smirnov (K-S) method of non-parametric test. The study findings suggest that small-scale fish farming in the study area has a significant positive impact on poverty reduction, as increase in each of the independent variables tends to increase the dependent variable. The paper recommended the establishment of fish farm settlements; granting of credit facilities to fish farmers as input factor’s promotion and enhancement of local content for fish farming among other policy prescriptions. These measures would promote small-scale fish farming for poverty reduction in the southeast geo-political zone of Nigeria.